2018
DOI: 10.3389/fnut.2018.00122
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Kyolic Aged Garlic Extract on Gut Microbiota, Inflammation, and Cardiovascular Markers in Hypertensives: The GarGIC Trial

Abstract: Background: Previous research suggests Kyolic-aged-garlic-extract to be effective in reducing blood pressure in a large proportion of hypertensive patients similar to first-line standard antihypertensive medication. High blood pressure has been linked to gut dysbiosis, with a significant decrease in microbial richness and diversity in hypertensives compared to normotensives. Furthermore, gut dysbiosis has been associated with increased inflammatory status and risk of cardiovascular events.Objective: To assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 47 publications
2
52
1
1
Order By: Relevance
“…The study by Okuhira, Holbert, Sandhu, and Steiner ((2000)) cited in Budoff et al (2009) was not published in Phytomedicine as stated and could not be (2002), Dillon, Lowe, Billington, and Rahman (2002), Ohnishi, Ohnishi, and Ogunmola (2000), Rahman and Billington (2000), Dimitrov and Bennink (1997), Abdullah et al (1989), Kawashima et al (1989, 1985, and Miyoshi et al (1984) were open and uncontrolled ( Figure 1a). We identified one further study in CENTRAL that lasted less than 8 weeks (Nagata et al, 2017); the other study identified was that of Ried, Travica, and Sali (2018), a candidate for extraction from the PubMed search (Figure 2a). The five congress contributions found in CENTRAL were later published as original articles.…”
Section: Aged Garlic (Age)mentioning
confidence: 99%
“…The study by Okuhira, Holbert, Sandhu, and Steiner ((2000)) cited in Budoff et al (2009) was not published in Phytomedicine as stated and could not be (2002), Dillon, Lowe, Billington, and Rahman (2002), Ohnishi, Ohnishi, and Ogunmola (2000), Rahman and Billington (2000), Dimitrov and Bennink (1997), Abdullah et al (1989), Kawashima et al (1989, 1985, and Miyoshi et al (1984) were open and uncontrolled ( Figure 1a). We identified one further study in CENTRAL that lasted less than 8 weeks (Nagata et al, 2017); the other study identified was that of Ried, Travica, and Sali (2018), a candidate for extraction from the PubMed search (Figure 2a). The five congress contributions found in CENTRAL were later published as original articles.…”
Section: Aged Garlic (Age)mentioning
confidence: 99%
“…These ndings suggested that anti-atherosclerotic effect of AGE may be attributable to its ability to protect and maintain the vascular endothelial barrier function. AGE has been reported to exert various pharmacological effects, such as anti-atherosclerotic [20,[22][23][24], anti-hypertensive [25,26] and anti-in ammatory effects [20,21], which are considered to be attributable to its sulfur-containing constituents. Therefore, we investigated whether S1PC, SAC and SAMC, three major sulfur-containing constituents in AGE, affect the endothelial barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Aged garlic extract (AGE) is a unique garlic preparation that is produced by aging of raw garlic in an aqueous ethanol solution for more than 10 months. AGE has been shown to exert various biological and pharmacological activities such as anti-in ammatory [20,21], anti-atherosclerotic [20,[22][23][24], antihypertensive [25,26] and anti-oxidative effects [27,28]. In particular, AGE prevented progression of cardiovascular diseases through the improvement of vascular endothelial dysfunction in clinical studies [24,26,[29][30][31][32].…”
mentioning
confidence: 99%
“…Accordingly, inflammation induces insulin resistance and hyperglycemia. Previous studies have suggested that AGE suppresses inflammation in clinical trials and animal studies (23,28,29,34). AGE has been shown to inhibit the expression of Ccl2/Mcp-1 mRNA in adipose tissue and liver of TSOD mice (34).…”
Section: Suppression Of Plasma Glycated Albumin Level and Induction Omentioning
confidence: 98%
“…Aged garlic extract (AGE) is produced by aging garlic (Allium sativum L.) in a water-ethanol mixture for >10 months at room temperature and contains several characteristic sulfur compounds, such as S-allylcysteine (SAC), S-1-propenylcysteine (S1PC) and S-allylmercaptocysteine (SAMC) (15,16). AGE has been shown to exert immunomodulatory effects (17)(18)(19)(20), anti-atherosclerotic effects (21)(22)(23)(24)(25), anti-hypertensive effects (26)(27)(28)(29), antioxidant effects (30)(31)(32) and blood flow-improving effects (33) in clinical and animal studies. In addition, recent studies have suggested that AGE and its components can induce the activation of AMPK in several cell types and tissues (19,23,(34)(35)(36)(37).…”
Section: Mechanisms Underlying the Attenuation Of Chronic Inflammatormentioning
confidence: 99%